Impact of Morus alba L. on the expression of drug-metabolizing enzymes and transporters in Caco-2 cells - Waranya Chatuphonprasert, Wipawee Tukum-mee, Jintanaporn Wattanathorn, Kanokwan Jarukamjorn (Journal of Applied Pharmaceutical Science, 2022)
Morus alba (MA) L. (mulberry) fruit has been consumed for a long time as a food and a source of vitamin C, anthocyanins, flavonoids, and alkaloids. The effects of MA fruit extract on drug-metabolizing genes and drug transporters were investigated in human colorectal adenocarcinoma cells. Cells treated with MA or its major bioactive constituents, rutin, and cyanidin-3-O-glucoside (C3G), were assessed for cell viability, production of reactive oxygen species (ROS), and alanine aminotransferase (ALT) and aspartate transaminase (AST) levels. The mRNA expression of target metabolic genes was determined using real-time polymerase chain reaction. Cell viability remained higher than 80%, and ROS levels were unchanged by all treatments. MA, C3G, and rutin did not alter the ALT and AST levels or expression of CYP2D6 and sulfotransferase 1A1 (SULT1A1). However, MA, C3G, and rutin down-regulated the expression of CYP2C19, CYP3A4, uridine diphosphate-glucuronosyltransferase 1A6 (UGT1A6), N-acetyltransferase 1, and organic anion transporting polypeptide 1B1 (OATP1B1), and MA elevated the expression of CYP1A2. In addition, MA induced CYP1A2 and CYP2C19 expression in combination with aspirin, caffeine, and simvastatin and upregulated expression of UGT1A6 and SULT1A1 in combination with paracetamol. Therefore, consumption of MA fruit or its supplements poses a risk for drug interactions via its modulation of cytochrome P450 and conjugation enzyme-associated metabolism and OATP1B1-mediated drug transport.
Keywords: Mulberry, cytochrome P450, rutin, cyanidin-3-O-glucoside, drug interaction